The Fireside Chats of Franklin Delano Roosevelt : Radio Addresses to the American People Broadcast Between 1933 and 1944 - Roosevelt, Franklin D. (Franklin Delano), 1882-1945 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Fireside Chats of Franklin Delano Roosevelt" by Franklin D. Roosevelt is a collection of radio addresses delivered to the American public between 1933 and 1944. Written during the Great Depression and World War II, these speeches aimed to inform, reassure, and engage the populace in the federal government$1 (Bs efforts to stabilize the economy and address national crises. The work reflects Roosevelt's effective communication style, emphasizing transparency, hope, and collective action. The opening of this compilation establishes Roosevelt$1 (Bs intent to ease public anxiety surrounding the banking crisis of 1933. In his first address, he explains the mechanics of banking, the rationale behind the national bank holiday, and the measures taken to restore public confidence in the banking system. Roosevelt acknowledges the hardships faced by citizens and calls for their collective cooperation to navigate the recovery process. He emphasizes the importance of consumer confidence in economic recovery and outlines a series of legislative actions aimed at stabilizing the financial system and stimulating the economy. This introductory portion sets the tone for the series of chats, underlining Roosevelt's commitment to the American people and his call for unity in overcoming challenges. (This is an automatically generated summary.)s
Release date is 2004-05-01
This etext was produced by Steve Bonner
Keywords: Roosevelt, Franklin D. (Franklin Delano), 1882-1945 -- Oratory -- Sources; Roosevelt, Franklin D. (Franklin Delano), 1882-1945 -- Political and social views -- Sources; Depressions -- 1929 -- United States -- Sources; New Deal, 1933-1939 -- Sources; World War, 1939-1945 -- United States -- Sources; United States -- Economic conditions -- 1918-1945 -- Sources; United States -- Economic policy -- 1933-1945 -- Sources; United States -- Politics and government -- 1933-1945 -- Sources; United States -- Foreign relations -- 1933-1945 -- Sources